Attitudes toward pre-symptomatic screening for Alzheimer’s dementia in five European countries: a comparison of family members of people with Alzheimer’s dementia versus non-family members - Angelidou, Ioanna A.; Makri, Marina; Beyreuther, Konrad; Boada Rovira, Mercè; Despoti, Akyllina; Engelborghs, Sebastiaan; Miguel, Andrea; Rodríguez, Isabel; Temmerman, Joke; Tsolaki, Magda; Yener, Görsev; Yerlikaya, Deniz; et al. (Frontiers in genetics, 2023)
Introduction: Pre-symptomatic screening is getting more attention in healthcare as it detects the risk for developing neurodegenerative diseases like Alzheimer’s disease (AD), which is very useful for treatment or prevention. AD screening could play an important role in individuals with at least one affected first-degree relative, but also without family history. As the demand for screening is rising worldwide, it is important to consider possible cross-cultural differences in attitudes toward pre-symptomatic screening in order to tailor healthcare services to the needs of each country. Objective: This study aims to investigate the attitudes of family members and nonfamily members of people with dementia toward pre-symptomatic screening and explore possible differences in attitudes across five European countries (Belgium, Germany, Greece, Spain, Turkey) using translated versions of the “Perceptions regarding pRE-symptomatic Alzheimer’s Disease Screening” questionnaire (PRE-ADS). Methods: The multicultural sample (N = 650) was recruited from samples that were previously used in validation studies of the translated PRE-ADS versions. The subscale “Acceptability of Screening”, consisting of five PRE-ADS items to specifically explore willingness to undergo screening, was created. Ιnternal consistency was measured, and structural validity was determined using Confirmatory Factor Analysis (CFA). Group comparisons were performed to investigate differences in attitudes toward pre-symptomatic AD screening regarding family history and country of origin using the PRE-ADS and the “Acceptability of Screening” mean scores. Results: Construct validity was acceptable for the PRE-ADS. Both the PRE-ADS (α = 0.76) and its subscale “Acceptability of Screening” (α = 0.90) had good internal consistency. Overall, 56.9% of the total sample expressed a positive intention toward pre-symptomatic AD screening. T-tests showed significantly higher mean scores of participants with an affected family member. An international comparison revealed differences in the “Acceptability of Screening” mean score across the five European countries. No cross-cultural differences were found for the PRE-ADS mean score after adjusting for confounding variables. Conclusion: The PRE-ADS and its subscale are reliable tools for assessing presymptomatic AD screening attitudes. Variations in the acceptability of screening seem to be linked to family history and cultural influences. Further research with larger samples is needed to explore underlying relationships.